2013
DOI: 10.1074/jbc.m113.481077
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Acyl-CoA Synthetase Isoform 4 Activity in INS 832/13 Cells Reduces Cellular Epoxyeicosatrienoic Acid Levels and Results in Impaired Glucose-stimulated Insulin Secretion

Abstract: Background:The role of intracellular lipid metabolism as it relates to nutrient-coupled glucose-stimulated insulin secretion has not been fully elucidated. Results: Knockdown of acyl-CoA synthetase isoform 4 impairs glucose-stimulated insulin secretion caused by decreased cellular epoxyeicosatrienoic acids. Conclusion: Acyl-CoA synthetase 4 is required for optimal glucose-stimulated insulin secretion. Significance: Understanding the role of beta-cell lipid metabolism is needed to develop novel strategies to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 48 publications
5
39
0
Order By: Relevance
“…Falck et al reported that 5,6-EET doubled insulin release from isolated rat pancreatic islets, compared with control values. [25] In contrast, Klett et al have reported that unesterified EETs decrease glucose-stimulated insulin secretion in isolated islets,[26] and we have found that glucosestimulated insulin secretion is increased in Cyp2c44 null mice, the equivalent of CYP2C8/9 in humans (unpublished data). In the current study, we do not find any relationship between either EPHX2 genotype or EETs and glucose-stimulated insulin secretion in humans.…”
Section: Discussionmentioning
confidence: 55%
“…Falck et al reported that 5,6-EET doubled insulin release from isolated rat pancreatic islets, compared with control values. [25] In contrast, Klett et al have reported that unesterified EETs decrease glucose-stimulated insulin secretion in isolated islets,[26] and we have found that glucosestimulated insulin secretion is increased in Cyp2c44 null mice, the equivalent of CYP2C8/9 in humans (unpublished data). In the current study, we do not find any relationship between either EPHX2 genotype or EETs and glucose-stimulated insulin secretion in humans.…”
Section: Discussionmentioning
confidence: 55%
“…We now propose that this increase in PUFA-TAGs is caused by an increase in ACSL4 during HSC activation. Likewise, knock down of ACSL4 in insulin secreting INS 832/13 cells inhibited the incorporation of labeled AA into TAGs but not into PLs [25]. In contrast, overexpression of ACSL4 in arterial smooth muscle cells caused a relatively larger increase in incorporation of labeled AA into PLs as compared to TAGs [20].…”
Section: Discussionmentioning
confidence: 93%
“…ACSL6, too, activates FA that are incorporated into phospholipids in neuronal cells (117), and an siRNA knockdown of Acsl1 reduces the levels of some phosphatidylcholine species that contain 20:4ω6 (93). In a related study in INS 832/13 cells, an siRNA knockdown of Acsl4 , but not Acsl5 , decreases basal and FA-stimulated glucose-stimulated insulin secretion by increasing the media content of epoxyeicosatrienoic acids (EETs) (91). In this study, the membrane content of EETs was reduced, suggesting that ACSL4 controls the intracellular content of unesterified EETs.…”
Section: Long-chain Acyl-coa Synthetasesmentioning
confidence: 99%